PENINGKATAN GERAKAN PSN DAN APLIKASI LARVASIDA NABATI DALAM MENGENDALIKAN JENTIK Aedes aegypti DI RW.12 KELURAHAN PASIRKALIKI KECAMATAN CIMAHI UTARA - Nurul Hidayah; Dindin Wahyudin (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2022)
Data on cases of Dengue Blood Fever (DHF) in the Pasirkaliki Village from 2019 to 2022 have increased, namely there are 45,387 cases. Dengue fever is transmitted through the vector of the Aedes aegypti mosquito which carries the dengue virus. Control of the Aedes aegypti mosquito vector can be started by eradicating the larvae or larvae before they develop into adult mosquitoes. Based on the results of a survey of Aedes aegypti larvae in RW 12, Pasirkaliki Village, conducted by the Pasirkaliki Health Center in collaboration with students majoring in Environmental Health, it was found that the larvae-free rate in RT 03 was 14.28% and in RT 01 was 21.42%, this shows very low compared to the standard from the government is> 95%. The use of environmentally friendly vegetable larvicides made from natural ingredients such as citronella, ginger and neem leaves can control Aedes aegypti larvae or mosquitoes. The purpose of this community service is to increase understanding of DHF, how to control it, implement and evaluate efforts to increase the larvae-free rate (ABJ), and apply the use of vegetable larvicides. The method of carrying out activities is through dissemination of understanding through pre-post tests regarding DHF and its control, observation to find out the larva-free number (ABJ) and the application of appropriate technology, namely the use of vegetable larvicides to cadres of RT 01 and RT 03. The results of the activity show that there is an average increase in knowledge pre-post respondents, namely RT 01 pre 45% post 68.5%, RT 03 pre 55.2% post 70.5%. There was an increase in the average larvae-free rate before and after PSN training was carried out, namely 89.88% in RT.01 and 94.89% in RT.03 RW.12, and the community was able to apply vegetable larvicide derived from natural ingredients in environment around the community.